2006
DOI: 10.1007/s00359-006-0171-0
|View full text |Cite
|
Sign up to set email alerts
|

Colour vision and visual ecology of the blue-spotted maskray, Dasyatis kuhlii Müller & Henle, 1814

Abstract: Relatively little is known about the physical structure and ecological adaptations of elasmobranch sensory systems. In particular, elasmobranch vision has been poorly studied compared to the other senses. Virtually nothing is known about whether elasmobranchs possess multiple cone types, and therefore the potential for colour vision, or how the spectral tuning of their visual pigments is adapted to their different lifestyles. In this study, we measured the spectral absorption of the rod and cone visual pigment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
130
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(138 citation statements)
references
References 52 publications
7
130
1
Order By: Relevance
“…The peak reflectance of the blue ring lies well within the range of mid-and long-wavelength sensitive opsins of potential marine vertebrate and invertebrate predators, including cetaceans, pinnipeds, birds, teleost fishes and other cephalopods (Hanlon and Messenger, 1996;Cronin et al, 2000;Hart, 2004;Levenson et al, 2006;Gacic et al, 2007;Theiss et al, 2007). Furthermore, the blue-green part of the visible spectrum is the most prominent ambient underwater light field (Tyler and Smith, 1970;Jerlov, 1976), so the iridescence is spectrally well tuned to be maximally visible.…”
Section: Discussionmentioning
confidence: 96%
“…The peak reflectance of the blue ring lies well within the range of mid-and long-wavelength sensitive opsins of potential marine vertebrate and invertebrate predators, including cetaceans, pinnipeds, birds, teleost fishes and other cephalopods (Hanlon and Messenger, 1996;Cronin et al, 2000;Hart, 2004;Levenson et al, 2006;Gacic et al, 2007;Theiss et al, 2007). Furthermore, the blue-green part of the visible spectrum is the most prominent ambient underwater light field (Tyler and Smith, 1970;Jerlov, 1976), so the iridescence is spectrally well tuned to be maximally visible.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, colour-opponent responses were recorded from horizontal cells in the retina of the red stingray, Dasyatis akajei (Toyoda et al, 1978), and recent MSP studies have reported the presence of up to three spectrally distinct cone types in three ray species, including G. typus (Hart et al, 2004;Theiss et al, 2007). The results obtained from the present study suggest that G. typus, and most likely other rays with multiple cone types, are capable of discriminating a coloured reward stimulus from a range of different coloured distracter stimuli of varying brightness.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for more than one spectral cone type in the ray retina, however, is more convincing, with studies indicating the presence of more than one photopic cone-based mechanism (Govardovskii and Lychakov, 1977;Toyoda et al, 1978). Recently, data obtained using MSP have indicated the presence of up to three spectrally distinct cone pigments in the retina of the giant shovelnose ray, Glaucostegus typus [wavelength of maximum absorbance ( max )477, 502 and 561nm], the eastern shovelnose ray, Aptychotrema rostrata ( max 459, 492 and 553nm) (Hart et al, 2004), and the bluespotted maskray, Neotrygon (Dasyatis) kuhlii ( max 476, 498 and 552nm) (Theiss et al, 2007). These findings raise the possibility that rays have a potentially trichromatic colour vision system.…”
Section: Introductionmentioning
confidence: 99%
“…LCA is greatest for short wavelengths of light (blue-ultraviolet), so it is possible that LCA may occur at wavelengths below the spectral range investigated in this study. Short wavelength image defocus would, however, be somewhat controlled by the transmission properties of the ocular media, which are opaque to wavelengths below 400nm (juvenile and adult S. mitsukurii) and below 310nm and 382nm for juvenile (65cm TL) and adult (142cm TL) C. plumbeus, respectively (Fig.5).Short wavelength-filtering ocular media, as shown in S. mitsukurii (Fig.5) , have been found in other elasmobranch species including the wobbegong shark Orectolobus ornatus (T 50 403nm) (Siebeck and Marshall, 2001), the grey reef shark, C. amblyrhynchos (T 50 400nm) , and several batoid species (T 50 402-437nm) (Siebeck and Marshall, 2001;Theiss et al, 2007). The light-filtering properties of the ocular media are attributed to a group of UV-absorbing pigments called mycosporinelike amino acids (MAAs), one of which, asterina-330, has been identified in shark lenses (Dunlap et al, 1989;Douglas and Marshall, 1999).…”
mentioning
confidence: 83%